An investigation into the parameters that contribute to the gap between the designed and as-built thermal performance of British housing - White, Jennifer A. (2014)
The UK Government has placed the need to reduce national energy demands and carbon emissions at the forefront of the political agenda, with a commitment made to meet EU targets of 20% reductions in greenhouse gas emissions and primary energy consumption, alongside a 20% improvement in overall energy efficiency, across all EU Member States, by 2020.